Enabling Medicago truncatula forward genetics: identification of genetic crossing partner for R108 and development of mapping resources for Tnt1 mutants. (1st June 2022) - Cheng, Xiaofei; Xie, Hongli; Zhang, Kuihua; Wen, Jiangqi
SUMMARY: Though Medicago truncatula Tnt1 mutants are widely used by researchers in the legume community, they are mainly used for reverse genetics because of the availability of the BLAST‐searchable large‐scale flanking sequence tags database. However, these mutants should have also been used extensively for forward genetic screens, an effort that has been hindered due to the lack of a compatible genetic crossing partner for the M. truncatula genotype R108, from which Tnt1 mutants were generated. In this study, we selected three Medicago HapMap lines (HM017, HM018 and HM022) and performed reciprocal genetic crosses with R108. After phenotypic analyses in F1 and F2 progenies, HM017 was identified as a compatible crossing partner with R108. By comparing the assembled genomic sequences of HM017 and R108, we developed and confirmed 318 Indel markers evenly distributed across the eight chromosomes of the M. truncatula genome. To validate the effectiveness of these markers, by employing the map‐based cloning approach, we cloned the causative gene in the dwarf mutant crs isolated from the Tnt1 mutant population, identifying it as gibberellin 3‐β‐dioxygenase 1, using some of the confirmed Indel markers. The primer sequences and the size difference of each marker were made available for users in the web‐based database. The identification of the crossing partner for R108 and the generation of Indel markers will enhance the forward genetics and the overall usage of the Tnt1 mutants. Significance Statement: We identified the Medicago truncatula HapMap line HM017 as a compatible crossing partner with the genotype R108 and Tnt1 mutants. We further developed more than 300 Indel markers with at least 100‐bp amplicon size difference between HM017 and R108. The developed resources are instrumental to enhancing the forward genetics of Tnt1 mutants.